Rancang Bangun E-Learning Universitas Janabadra Menggunakan Efront - Marciano De Jesus Soares; Jemmy Edwin Bororing; Fatsyahrina Fitriastuti (Informasi Interaktif, 2016)
Living in modern times sophisticated demands forced the man to always learn. Learning one human needs. Learning the process of filling the soul with knowledge and experience as much as possible. Learning does not merely have to come to school, sit down with more friends in the class. The development of information technology so rapidly bring great influence in various fields, especially in education. This study builds a system that can support teaching and learning at the Janabadra University.The study was conducted using a system associated with the application of e-learning, also use some libraries and software that is used as a research tool. Using eFront as software. EFront a Learning Management System platform built using the PHP programming language, as a server side scripting. Apache as a web server, and MySQL as the database server, as well as other supporting applications (Dreamweaver CS5 and Notepad ++), to design the display using HTML, and AJAX as client side scripting for interaction with the user, as well as the browser Mozilla Firefox, Google Chrome and Opera to display page to the user.The study resulted in an e-learning application designed to provide ease - the ease required by students and faculty for smooth academic activities lecture, which is expected to address the needs of students and teachers will a lecture or learning system that is not limited by space and time. The test result of system users stated that e-learning applications can run well and according to user needs. Keywords: E-Learning, Learning Management System, EFront, Virtual learning environment.